A Novel Design and Implementation of 8-3 Encoder Using Quantum-dot Cellular Automata (QCA) Technology - Md. Sofeoul-Al-Mamun; Mohammad Badrul Alam Miah; Fuyad Al Masud (European Scientific Journal, ESJ, 2017)
In recent years Quantum-dot Cellular Automata (QCA) has been considered one of the emerging nano-technology for future generation digital circuits and systems. QCA technology is a promising alternative to Complementary Metal Oxide Semiconductor (CMOS) technology. Thus, QCA offers a novel electronics paradigm for information processing and communication system. It has attractive features such as faster speed, higher scale integration, higher switching frequency, smaller size and low power consumption compared to the transistor based technology. It is projected as a promising nanotechnology for future Integrated Circuits (ICs). A quantum dot cellular automaton complex gate is composed from simple 3-input majority gate. In this paper, a 8-3 encoder circuit is proposed based on QCA logic gates: the 4-input Majority Voter (MV) OR gate. This 7-input gate can be configured into many useful gate structures such as a 4-input AND gate, a 4-input OR gate, 2-input AND and 2-input OR gates, 2-input complex gates, multi-input complex gates. The proposed circuit has a promising future in the area of nano-computing information processing system and can be stimulated with higher digital applications in QCA.